2020
DOI: 10.4028/www.scientific.net/kem.842.121
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO<sub>2</sub> Thin Films by Sol-Gel Method and Analysis of its Transmittance Based on Computer Image Processing

Abstract: TiO2 films were prepared by sol-gel method with butyl titanate, anhydrous ethanol, acetyl acetone and hydrochloric acid as raw materials, which were sintered at 380 °C and 530 °C respectively to obtain TiO2 films. XRD was used for analyzing the crystal structure of TiO2 film, and ImageJ software was used to detect the light transmittance of TiO2 film samples. The results show that the film sintered at 530 °C is brookite structure and the film sintered at 380 °C is anatase structure. The increase of sintering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that TiO2 film is brookite and the diffraction peaks of XRD will move to the right when the heat treatment temperature reaches 530 ℃ [15]. However, after adding Lu and heating at 550 ℃, the crystal form of TiO2 films does not change to brookite, indicating that the addition of Lu inhibits the occurrence of brookite.…”
Section: Fig 3 Xrd Patterns Of Lu-doped Tio2 and Pure Tio2 Filmsmentioning
confidence: 92%
“…Previous studies have shown that TiO2 film is brookite and the diffraction peaks of XRD will move to the right when the heat treatment temperature reaches 530 ℃ [15]. However, after adding Lu and heating at 550 ℃, the crystal form of TiO2 films does not change to brookite, indicating that the addition of Lu inhibits the occurrence of brookite.…”
Section: Fig 3 Xrd Patterns Of Lu-doped Tio2 and Pure Tio2 Filmsmentioning
confidence: 92%